Pengembangan E-Court di Pengadilan Agama Bangil - Andre Oktaviano; Fitrotun Nuzula; Kurniasari, Lailatul Urifah; Lulu Sakina, Mamlu’atul Kiftiyah (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2020)
Abstract: Technological progress is very rapid, especially in the field of information technology, such as the internet, smart cities, big data, and artificial intelligence has provided convenience in efforts to improve the quality of access to electronic-based service systems of various things. intended for modern society. Technological developments have provided positive benefits. The Supreme Court of the Republic of Indonesia as a justice system in Indonesia has provided the latest innovation by issuing an e-court service system. E-court has a positive impact on society as a means to register cases that are evidence of the commitment of the Supreme Court of the Republic of Indonesia to realize electronic court as a form of modern court that applies fast, simple and low cost principles. In the case of e-online filling all registration files are sent electronically including e-SKUM and e-payment. This is of course based on the regulations of the Supreme Court of the Republic of Indonesia Number 3 of 2018. Although Indonesia's e-court services are quite new, and lag behind other countries such as Singapore, this step is considered appropriate for people who need a quick process in registering cases. Based on PERMA's e-court, advocates are asked to register to facilitate the dispute resolution process in the e-court system and become an absolute requirement to be able to represent their clients. However, there are several conditions that must be carried out by lawyers and only lawyers who have been legally recognized. Keywords: e-court, e-court registration, weakness of e-court.   Abstrak: Kemajuan teknologi sangat pesat, terutama di bidang teknologi informasi, seperti internet, kota pintar, data besar, dan kecerdasan buatan telah memberikan kemudahan dalam upaya meningkatkan kualitas akses ke sistem layanan berbasis elektronik dari berbagai hal, ditujukan untuk masyarakat modern. Perkembangan teknologi telah memberikan manfaat positif. Mahkamah Agung Republik Indonesia sebagai sistem peradilan di Indonesia telah memberikan inovasi terbaru dengan mengeluarkan sistem layanan pengadilan elektronik. E-court memiliki dampak positif pada masyarakat sebagai sarana untuk mendaftarkan kasus-kasus yang merupakan bukti komitmen Mahkamah Agung Republik Indonesia untuk mewujudkan pengadilan elektronik sebagai bentuk pengadilan modern yang menerapkan prinsip-prinsip cepat, sederhana dan berbiaya rendah. Dalam hal pengisian e-online, semua file pendaftaran dikirim secara elektronik termasuk e-SKUM dan pembayaran elektronik. Hal ini tentu saja berdasarkan pada peraturan Mahkamah Agung Republik Indonesia Nomor 3 Tahun 2018. Meskipun layanan e-court Indonesia cukup baru, dan tertinggal dari negara lain seperti Singapura, langkah ini dianggap sesuai untuk orang yang membutuhkan proses cepat dalam mendaftarkan kasus. Berdasarkan e-court PERMA, para advokat diminta mendaftar untuk memfasilitasi proses penyelesaian sengketa dalam sistem e-court dan menjadi persyaratan mutlak untuk dapat mewakili klien mereka. Namun, ada beberapa syarat yang harus dilakukan oleh pengacara dan hanya pengacara yang telah diakui secara hukum. Kata kunci: e-court, pendaftaran e-court, kelemahan e-court.